Expanding Transparent Covalently Attached Liquid‐Like Surfaces for Icephobic Coatings with Broad Substrate Compatibility - Amirhossein Jalali Kandeloos; Tanja Eder; Daniel Hetey; Alexander Bismarck; Michael R. Reithofer; Megan J. Cordill; Jia Min Chin (Advanced Materials Interfaces, 2025)
Abstract Ice accretion causes significant energy losses and safety risks across various sectors. Recent research shows that liquid‐like surfaces (LLS) with ice‐shedding properties can be created by covalently attaching linear polymer chains onto smooth substrates with sufficient hydroxyl group densities. To expand the substrate scope for LLS, a novel system using non‐halogenated organosilanes attached to a commercial epoxy‐silicon (EpSi) coating is proposed. The EpSi layer, easily applied using simple methods, serves as a smooth intermediate layer (Ra = 0.94 nm and Rq = 0.76 nm). Air plasma activation increases hydroxyl density on EpSi, enabling LLS formation via simple immersion in an organosilane solution. The resulting coating exhibits low contact angle hysteresis (<10°), sliding angle (SA < 14°), and ice adhesion strength (τice < 20 kPa). Effective LLS is generated regardless of substrate type, coating thickness, or application method. The coating retains its slippery properties after exposure to harsh conditions, including icing/deicing cycles, organic solvents, and acidic environment. It is also highly transparent (Tave = 84.5%, t = 500 µm) with self‐cleaning and anti‐staining capabilities. This methodology broadens the substrate scope of LLS, offering a sustainable solution to ice accretion challenges.